EVALUASI METODE REWARD AND PUNISHMENT UNTUK KEDISIPLINAN SISWA DI MI MUHAMMADIYAH PEBAUN HILIR KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Indriati Adni; Bustanur Bustanur; Andrizal Andrizal (Universitas Islam Kuantan Singingi, 2022)
The provision of stimulus from educators in the form of reward and punishment greatly affects the way of thingking and behavior of students in achieving the goals of character education or discipline that have been determined. The purpose of this research is how are the result of the evaluation of the application of the reward and punishment method for student discipline.This study uses a qualitative descriptive approach, so the presence of researchers in the field is very imponerthant. As for the data obtained throught observation, interviews and documentation, This data was obtained from informant, namely principals, classroom teachers and student. Data analysis is carried out by means of data reduction, data presentation, and data verification. The result obtained indicate that: 1) The evaluation of the reward and punishment method for student discipline at MI Muhammadiyah Pebaun downstream can be said to be good. 2) As a follow-up in evaluating the reward and punishment method at MI Muhammadiyah Pebaun downstream, teachers are expected to be more interesting forms of reward and punishment, and can be further developed in the long term to have a more real impact on student development.